Si Gabby Application (Student Learning System) to Improve Student's Learning Achievement in IPS Courses in Learning Activity Studio - Erlangga, Erwin; Sugiarti, Rini; Daru, April Firman; Desyantoro, Irwan; Veronika, Nofita (Journal of Nonformal Education, 2022)
The ultimate goal of this research is the arrangement of the SI - Gabby application (Student Learning System) to improve student achievement. The application framework is prepared based on theoretical, empirical studies, and objective conditions of the implementation of the school learning system at Learning Activity Studio (SKB) Therefore, this study uses research and development methods and designs based on the principles and steps of Borg Gall. The population is 360 people, the sample is 230 people. Data collection techniques using purposive sampling. Data collection tool using a psychological scale. Based on the analysis of the implementation process of the developed model as well as the results achieved by group members, it proves that the student learning system is effective in improving student achievement. Indications of the success of the service implementation process can be seen from the roles carried out by counselors and group members at each stage, both the formation, transition, activity, and termination stages where at the activity stage the counselor applies the stages of the online learning system so that it is well internalized to all members of the group. While the effectiveness of the service is evidenced by the results of the achievement scale which shows an increase in the results of the initial evaluation and final evaluation on the total score of achievement.